Should age be a deciding factor of selection for admission in a Rehabilitation Centre after Stroke? - Caetano, Pedro Francisco dos Santos (2019)
Aims: Stroke represents one of the main causes of mobility and mortality, occurring in three-quarters of the elderly. Rehabilitation aims at improving deficits, function and social integration of patients with stroke sequelae. We characterized an elderly population admitted for post-stroke rehabilitation and evaluated the differences in the functional evolution between elderly and non-elderly patients.Methods: We analyzed retrospectively all the patients suffering a stroke admitted in a Centre of Rehabilitation Medicine between June 1, 2014, and May 31, 2016. Patients were divided into 2 groups: elderly (65 years) and non-elderly (<65 years). The following variables were analyzed: sex, age, days of admission, post-discharge destination and Functional Independence Measure (FIM) at admission and discharge.Results: We analyzed 134 patients with stroke. The majority were elderly with a mean age of 72.07±6.50. 51.3% were men and the number of days of admission was 107.4±59.5 (vs 109.50±55.7 days in the non-elderly group). 86.4% of these patients were discharged home. Comparing FIM mean values at admission and discharge, we found differences between these two groups, the elderly patients having lower FIM values at admission (75.75 vs 82.96 non-elderly; p=0.005) and at discharge (88.93 vs 99.12 non-elderly; p=0.005). There was also some difference in the FIM increase between admission and discharge in these groups. Despite not being statistically significant.Conclusions: Most patients hospitalized were over 65 years old. FIM values at admission of the elderly patients are lower than of the non-elderly, probably because the latter present specific characteristics associated with the ageing process. Although FIM increases were lower in the elderly patients’ group, this difference was not significant whereby they appeared to have functionally benefited as much as the non-elderly. Therefore, age on its own does not appear to be a decision criteria for admission.